Social Change of Traditional Communities in the Direction of Modernization in the Anthropological Approach to Law - Emy Handayani (Musamus Law Review, 2019)
The social change of the Dago Pojok Bandung Creative Village community is one way to preserve traditional villages as a creative village that adapts to the development of times in today's modern society. The empirical approach in the study of legal Anthropology which explains that traditional/modern society has a very large influence in the lives of social change in society to achieve progress. The Comparative Approach to Legal Anthropology explains that in traditional/modern societies a rule is needed that governs the lives of its people. The change of traditional society should be addressed to the good for the good of the next generation in social life through norms, behavior that avoids the deviations of traditional/modern social change.